Severe Calorie Restriction Reduces Cardiometabolic Risk Factors and Protects Rat Hearts from Ischemia/Reperfusion Injury - Melo, Dirceu S.; Costa-Pereira, Liliane V.; Santos, Carina S.; Mendes, Bruno F.; Costa, Karine B.; Santos, Cynthia Fernandes F.; Rocha-Vieira, Etel; Magalhães, Flávio C.; Esteves, Elizabethe A.; Ferreira, Anderson J.; Guatimosim, Sílvia; Dias-Peixoto, Marco F. (Frontiers in Physiology, 2016)
Background and Aims: Recent studies have proposed that if a severe caloric restriction (SCR) is initiated at the earliest period of postnatal life, it can lead to beneficial cardiac adaptations later on. We investigated the effects of SCR in Wistar rats from birth to adult age on risk factors for cardiac diseases (CD), as well as cardiac function, redox status and HSP72 content in response to ischemia/reperfusion (I/R) injury. Methods and Results: From birth to the age of 3 months, CR50 rats were fed 50% of the food that the ad libitum group (AL) was fed. Food intake was assessed daily and body weight were assessed weekly. In the last week of the SCR protocol, systolic blood pressure and heart rate were measured and the double product index was calculated. Also, oral glucose and intraperitoneal insulin tolerance tests were performed. Thereafter, rats were decapitated, visceral fat was weighed, and blood and hearts were harvested for biochemical, functional, tissue redox status and western blot analyzes. Compared to AL, CR50 rats had reduced the main risk factors for CD. Moreover, the FR50 rats showed increased cardiac function both at baseline conditions (45% > AL rats) and during the post-ischemic period (60% > AL rats) which may be explained by a decreased cardiac oxidative stress and increased HSP72 content. Conclusion: SCR from birth to adult age reduced risk factors for CD, increased basal cardiac function and protected hearts from the I/R, possibly by a mechanism involving ROS.